The Influence of Genotype on the Cardiopulmonary Test Response in Patients Affected by Hypertrophic Cardiomyopathy - Maria Felicia Gagliardi; Gabriella Malfatto; Claudia Baratto; Alessia Giglio; Valeria Rella; Paolo Cerea; Davide Mariani; Sabrina Salerno; Silvia Ravaro; Silvia Castelletti; Gerardina Fratianni; Chiara Alberio; et al. (Cardiogenetics, 2025)
In hypertrophic cardiomyopathy (HCM), the presence of pathogenic/likely pathogenic (P/LP) disease-causing genetic variants may indicate a worse prognosis. Few data exist on the effects of these genetic variants on cardiopulmonary exercise test (CPET) performance in HCM patients. We analysed asymptomatic and slightly symptomatic HCM patients (NYHA I-II) whose genetic analysis and CPET were available; at baseline, left ventricular function was normal and severe left ventricular outflow trait obstruction was excluded. Out of 120 HCM patients, we excluded 13 carrying variants of uncertain significance; of the remaining 107 patients, 54 were genotype negative [gene (−)], and 53 had a P/LP variant in sarcomeric genes [gene (+)]. Patients in the two groups had similar NYHA class, cardiovascular risk factors and echocardiographic characteristics. Gene (+) patients showed a lower peak VO2% and O2 pulse % (p < 0.05). Moreover, among gene (+), patients with P/LP variants in the so called “thin-filament” genes (TNNT2, TPM1 and MYL3) had the poorest CPET results. In asymptomatic or slightly symptomatic HCM patients with similar echocardiographic characteristics, exercise tolerance is affected by the genetic background. Indeed, exercise capacity is poorer in gene (+) compared to gene (−) patients and those carrying P/LP variants in “thin-filament” genes show the worst performance.